2021
DOI: 10.1186/s12887-021-02899-3
|View full text |Cite
|
Sign up to set email alerts
|

Obesity determinants among Malaysian 12-year old school adolescents: findings from the HAT study

Abstract: Background Childhood obesity has been associated with increased odds of adult obesity and co-morbidities in later life. Finding the key determinants may help in designing the most appropriate and effective interventions to prevent obesity. This study aimed to identify the determinants of obesity among school adolescents in a sub-urban state of Malaysia. Methods This cross-sectional study involved 1,404 school adolescents aged 12 years (46% boys and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 35 publications
1
8
0
Order By: Relevance
“…The convenient and constant self-tracking function would also encourage sustaining the newly adopted healthy lifestyle, including a higher number of walk counts (Attig et al, 2019). The introduction of wearable devices, therefore, offers a new possibility for effective technology intervention to promote physical activity (Naglis & Bhatiasevi, 2019) due to physical inactivity being the largest risk factor contributing to the prevalence of diabetes in Malaysia (Ahmad et al, 2021;WHO, 2016).…”
Section: Health Behaviourmentioning
confidence: 99%
“…The convenient and constant self-tracking function would also encourage sustaining the newly adopted healthy lifestyle, including a higher number of walk counts (Attig et al, 2019). The introduction of wearable devices, therefore, offers a new possibility for effective technology intervention to promote physical activity (Naglis & Bhatiasevi, 2019) due to physical inactivity being the largest risk factor contributing to the prevalence of diabetes in Malaysia (Ahmad et al, 2021;WHO, 2016).…”
Section: Health Behaviourmentioning
confidence: 99%
“…This is due to the high energy content in food and drinks, which results in a positive energy balance [ 11 ]. A study on school adolescents in Malaysia found that consuming dairy products and milk among adolescents was positively associated with obesity [ 12 ]. The quality of the diet is also associated with the risk of obesity and the correlation between dietary habits and the prevalence of overweight and obesity has been well-established in the literature [ 13 ].…”
Section: Risk Factorsmentioning
confidence: 99%
“…Research has shown that higher pre-pregnancy BMI directly correlates with childhood obesity [ 24 ]. It has also been found that parental BMI can substantially affect their children’s body weight [ 12 ]. It is thought that fetal growth contributes to the development of lean body mass later in life, making intrauterine life an important period for developing childhood obesity [ 25 ].…”
Section: Risk Factorsmentioning
confidence: 99%
See 1 more Smart Citation
“…Cross-sectional associations are also seen between parent and child body mass index (BMI), with stronger associations for those children with higher BMIs, suggesting an intergenerational transmission of risk for a high BMI [ 16 , 17 ]. Maternal pre-pregnancy BMI is prospectively associated with offspring BMI in both childhood and adulthood [ 18 ], but it is not clear whether associations are gender-specific, with some studies showing a stronger maternal association [ 17 , 19 ] while others show no differences between mothers and fathers [ 14 , 20 , 21 ]. Most studies of obesity prevalence are in high income countries, and systematic reviews suggest weaker associations in LMICs [ 14 , 15 ].…”
Section: Introductionmentioning
confidence: 99%